Effects of Question Methods in Assessing Fear of Hate Crimes - Pyo, Jimin (Crime & delinquency, 2025)
This study examined episodic measures that assess frequency and magnitude of perceived threat of hate crime over the last six months compared to standard methods that address diffuse threat. Framing effects of question wording, worry- versus fear- versus safety-based, were also assessed. Using Amazon?s Mechanical Turk, a sample of 1,824 adults vulnerable to hate crime completed one of the three randomly assigned survey questionnaires that varied the question wording. Results show that standard measures tend to yield higher levels of perceived threat of hate crime across different bias motivations than episodic measures. Worry- and fear-based questions were also associated with higher odds of perceived threat of hate crime than safety-based questions. Findings, implications, and future directions are discussed.